Vitamin D deficiency is a risk factor for delayed tooth eruption associated with persistent primary tooth. (17th November 2021) - Xavier, Thaís Aparecida; Madalena, Isabela Ribeiro; da Silva, Raquel Assed Bezerra; da Silva, Léa Assed Bezerra; Silva, Marcelo José Barbosa; De Rossi, Andiara; Küchler, Erika Calvano; Fukada, Sandra Yasuyo
Abstract: Objective: To verify the association between 25(OH)D level and polymorphisms in the vitamin D receptor gene ( VDR ) with the disturbance in the dental development and eruption. Design: A total of 183 children from two datasets were evaluated. The first dataset was a case–control (15:15) designed to assess if persistent primary tooth (PPT) is associate with serum 25(OH)D level and with genetic polymorphisms in VDR . The second dataset of genomic DNA samples from 54 children with delayed tooth eruption (DTE) and 99 controls were analysed to verify if genetic polymorphisms in VDR (rs2228570 and rs739837) are associated with DTE. The 25(OH)D and the genotyping/allele distribution were analysed using the T -test and chi-square test, respectively. Results: The level of 25(OH)D in the PPT group (24.9 ± 6.4 mg/mL) was significantly lower than the control (30.0 ± 7.0 mg/mL) ( p =.047). Our data show that children with 25(OH)D deficiency are more likely to present PPT (OR = 2.36; 95%CI: 1.51, 3.70). The rs739837 and rs2228570 polymorphisms were not associated with DTE (OR = 1.44; 95%CI: 0.87, 2.39 and OR = 0.80; 95%CI: 0.45, 1.44, respectively). Conclusions: Vitamin D deficiency is a risk factor for PPT.